(untitled) (Czech Journal of Multidisciplinary Innovations, 2025)
The research investigates the role of digital marketing strategies in enhancing the attractiveness of emerging tourist destinations. It explores the evolution of digital marketing, its components, and its impact on consumer behavior within the tourism industry. The study highlights how tools such as social media, search engine optimization (SEO), and digital advertising influence tourists’ decisions and improve the visibility of lesser-known destinations.